2003
DOI: 10.1095/biolreprod.102.011288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estrogen on Vascular Endothelial Growth/Permeability Factor Expression by Glandular Epithelial and Stromal Cells in the Baboon Endometrium1

Abstract: The ovarian steroid hormones, estrogen and progesterone, have important roles in establishing the new vascular bed within the endometrium during each menstrual cycle; however, little is known about the mechanisms underlying this process. We recently showed that mRNA and protein levels for the angiogenic factor vascular endothelial growth/permeability factor (VEG/PF) in endometrial glandular epithelial and stromal cells of baboons were decreased to very low levels by ovariectomy, and we proposed that the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…In addition, Nayak and Brenner also showed that estrogen stimulated endometrial VEGF expression in vivo in ovariectomized rhesus monkeys [43]. Therefore, combined with the present study, evidence supports that estrogen has a significant role in stimulating VEGF system expression by glandular, luminal epithelial and stromal cells of the endometrium to promote its angiogenesis and growth [44].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, Nayak and Brenner also showed that estrogen stimulated endometrial VEGF expression in vivo in ovariectomized rhesus monkeys [43]. Therefore, combined with the present study, evidence supports that estrogen has a significant role in stimulating VEGF system expression by glandular, luminal epithelial and stromal cells of the endometrium to promote its angiogenesis and growth [44].…”
Section: Discussionsupporting
confidence: 85%
“…Vegfa expression increased in endometrial stromal cells within 2 h. By 24 h post-administration, there was no stromal Vegfa and expression was restricted to the epithelium. In the baboon and rhesus monkey, endometrial stromal and epithelial VEGFA expression was restored by E 2 treatment following a reduction after ovariectomy (Nayak & Brenner 2002, Niklaus et al 2003. In baboon endometrium, VEGFA mRNA levels were increased in both stromal and glandular epithlelium (measured in samples collected by laser capture microscopy) within 2 h of E 2 administration and remained elevated during the 6 h experiment (Aberdeen et al 2008).…”
Section: Vascular Endothelial Growth Factor-amentioning
confidence: 97%
“…In vivo research with various animal models has produced more variable results. In studies using baboons and rhesus monkeys, endometrial stromal and epithelial VEGFA mRNA levels were restored by E 2 following a reduction after ovariectomy (Nayak & Brenner 2002, Niklaus et al 2003. In contrast, another study found that there was a significantly higher amount of VEGFA mRNA in endometria of hypogonadal monkeys compared with E 2 -treated monkeys (Greb et al 1997).…”
Section: Introductionmentioning
confidence: 96%